Dose-dependent relationship between acidosis at birth and likelihood of death or cerebral palsy. Issue 6 (8th December 2017) - Kelly, Rod; Ramaiah, SM; Sheridan, Helen; Cruickshank, Hilary; Rudnicka, Magda; Kissack, Chris; Becher, Julie-Clare; Stenson, Ben J
Abstract : Background: The acid-base status of infants around birth can provide information about their past, current and future condition. Although umbilical cord blood pH <7.0 or base deficit ≥12 mmol/L is associated with increased risk of adverse outcome, there is uncertainty about the prognostic value of degree of acidosis as previous studies have used different variables, thresholds, outcomes and populations. Methods: Retrospective review of routinely collected clinical data in all live-born inborn infants of 35 weeks gestation or more delivered between January 2005 and December 2013 at the Simpson Centre for Reproductive Health, Edinburgh, UK. Infants were included if their lowest recorded pH was <7 and/or highest base deficit ≥12 mmol/L on either umbilical cord blood and/or neonatal blood gas within 1 hour of birth. Neurodevelopmental outcome of the infants with encephalopathy was collected from the targeted follow-up database. Results: 56 574 infants were eligible. 506 infants (0.9%) met inclusion criteria. Poor condition at birth and all adverse outcomes increased with worsening acidosis. Combined outcome of death or cerebral palsy was 3%, 10% and 40% at lowest pH of 6.9–6.99, 6.8–6.89 and <6.8,  respectively, and 8%, 14% and 59% at a base deficit of 12–15.9, 16–19.9 and 20 mmol/L or more, respectively. Conclusions: There is a dose-dependent relationship between the degree of acidosis within an hour of delivery, and the likelihood of adverse neonatal and later neurodevelopmental outcome in infants born at 35 weeks gestation or more.